Continuous batch synthesis with atmospheric-pressure microwave plasmas - Ziyao Jie; Tian-Yu Wang; Shiyang Huang; Xinpeng Bai; Wenhui Ma; Guixin Zhang; Nan Luo (iScience, 2024)
Summary: Plasmas under atmospheric pressure offer a high-temperature environment for material synthesis, but electrode ablation compromises purity. Here, we introduce an atmospheric-pressure microwave plasma (AMP) operated without electrodes to overcome the existing limitations in pure material synthesis. The distribution of the electrostatic field intensity inside a waveguide during AMP excitation was examined via electrostatic field simulations. The lateral and radial gas temperature distributions were also studied using optical emission spectroscopy. The AMP exhibited a uniform ultrahigh temperature (9,000 K), a large volume (102–104 cm3), and a response time on the millisecond level. AMP efficiently synthesized silicon nanoparticles, graphene, and graphene@Si–Fe core-shell nanoparticles within tens of milliseconds, ensuring purity and size control. We propose the “heat impulse” metric for evaluating the plasma characteristics (na, Tg, and t) in material synthesis, extended to other high-temperature plasmas. AMP is compact, cost-effective, and easy to assemble, promising for eco-friendly mass production of pure materials.